Thyroid hormone suppresses hepatocarcinogenesis via DAPK2 and SQSTM1-dependent selective autophagy. Issue 12 (1st December 2016) - Chi, Hsiang-Cheng; Chen, Shen-Liang; Tsai, Chung-Ying; Chuang, Wen-Yu; Huang, Ya-Hui; Tsai, Ming-Ming; Wu, Sheng-Ming; Sun, Cheng-Pu; Yeh, Chau-Ting; Lin, Kwang-Huei
ABSTRACT: Recent studies have demonstrated a critical association between disruption of cellular thyroid hormone (TH) signaling and the incidence of hepatocellular carcinoma (HCC), but the underlying mechanisms remain largely elusive. Here, we showed that disruption of TH production results in a marked increase in progression of diethylnitrosamine (DEN)-induced HCC in a murine model, and conversely, TH administration suppresses the carcinogenic process via activation of autophagy. Inhibition of autophagy via treatment with chloroquine (CQ) or knockdown of ATG7 (autophagy-related 7) via adeno-associated virus (AAV) vectors, suppressed the protective effects of TH against DEN-induced hepatic damage and development of HCC. The involvement of autophagy in TH-mediated protection was further supported by data showing transcriptional activation of DAPK2 (death-associated protein kinase 2; a serine/threonine protein kinase), which enhanced the phosphorylation of SQSTM1/p62 (sequestosome 1) to promote selective autophagic clearance of protein aggregates. Ectopic expression of DAPK2 further attenuated DEN-induced hepatoxicity and DNA damage though enhanced autophagy, whereas, knockdown of DAPK2 displayed the opposite effect. The pathological significance of the TH-mediated hepatoprotective effect by DAPK2 was confirmed by the concomitant decrease in the expression of THRs and DAPK2 in matched HCC tumor tissues. Taken together, these findings indicate that TH promotes selective autophagy via induction of DAPK2-SQSTM1 cascade, which in turn protects hepatocytes from DEN-induced hepatotoxicity or carcinogenesis.